A Solution Method for Many-Objective Security-Constrained Unit Commitment Considering Flexibility - Lin, Shunjiang; Wu, Hui; Liu, Jie; Liu, Wanbin; Liu, Yanghua; Liu, Mingbo (Frontiers in Energy Research, 2022)
With the increasing penetration of wind power into power systems and the random fluctuation of wind farm (WF) output, system flexibility must be considered in the optimal generation dispatch. Based on the extreme scenarios of WF output, we proposed a flexibility risk index to evaluate the system flexibility of each time interval. We established a five-objective security constrained unit commitment (SCUC) model of a power system with WFs, thermal generation plants, battery energy storage stations, and pumped storage hydro stations. The objectives were to minimize the system flexibility risk, total network loss, operation cost, power purchase cost, and pollutant gas emissions. To obtain the Pareto optimal solutions of the model, based on the objective-selection and ε-constraint methods, we proposed two methods to reduce the dimension of objectives and transformed the five-objective optimization model into a series of three-objective optimization models. Then we used the normalized normal constraints method to solve the Pareto frontier surface of each three-objective optimization model. We used a color column to represent the value change of the two upper-layer objectives and visualized the Pareto frontier of the five-objective SCUC model in the three-dimensional ordinate space. Case studies on the modified IEEE-9 bus system and an actual power grid demonstrated the effectiveness and high computational efficiency of the proposed method.